PERANCANGAN SISTEM INFORMASI LAYANAN GADAI EMAS MENGGUNAKAN MICROSOFT VISUAL STUDIO PADA BANK SYARIAH INDONESIA KC CIMAHI - Mawardi, Zahra Nabilah; Muthmainnah; Kurniawati, Rina (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Bank Syariah Indonesia is a bank that emerged from a merger between PT Bank BRI Syariah Tbk, PT Bank Syariah Mandiri, and PT Bank BNI Syariah. The consolidation between the three Islamic banks resulted in more complete services, greater coverage, and more optimal funding capacity. One of the services from BSI is the Gold Pawn Service, which is a lending product based on gold as collateral as a practical way to obtain cash. The purpose of the research that designed the Gold Pawn Service information system was to facilitate recording and reporting of all activities in the Gold Pawn Service. Technology in designing the Gold Pawn Service information system using Microsoft Visual Studio with Microsoft Access as database. This research resulted in the design of a Gold Pawn Service financing simulation information system that features news information and knowledge about calculations and explanations of gold pawn service financing products at Bank Syariah Indonesia at Cimahi Branch Office.